Dinámica poblacional de antichloris viridis druce lepidóptera ctenuchidae en la temporada fría en la zona de Caña Quemada - Morales Gonzáles, Milton Oswaldo (2012)
he present investigation work on the populational dynamics of Antichloris viridis Druce (Lepidóptera, ctenuchidae) in the cold season, in the area of burnt cane he/she was carried out, in the parish Burnt Cane, of the canton Pasaje, province of El Oro, in the Hcda. Celia María S.A from the point of view of the density of larvas in the leaf eight and of their natural enemies. The objectives outlined in this investigation were: 1. Monitorear the generations of Caterpillar in the season of August to December and of their natural enemies, determining the indicators that allow to determine the type of Space Distribution. 2. to determine the model probabilísticos that better they are adjusted to the information gathered in the field to explain the interrelations with the climatic factors and bióticos of the study area. The region where it is pierced the banana tree plantations, it corresponds to a formation ecological Tropical dry forest (bs-T), with a biotemperatura of 26,5 centigrade grades, a Located annual half precipitation of 760 mm. the sampling places in the side of the left and right of the funicular one five plants were located without cluster spaced at least to 20 meters that it presents damages taken place by larvas. The eighth leaf intersected in the base with the podón, allowing that the descent of this of he/she takes place gently without the fall of larvas takes place. Then the leaf was placed on the floor with the back up with the purpose of to visualize and to count the number of larvas according to the size: 0,5 to 2,0 cm and> 2,5 cm; presence of natural control caused by Meteorus sp, Elachertus ceramidae, and Cassinaria. The monitoreo of adults of Antichloris viridis leaves like it is that the biggest index registers them the female insects, with 382 representing 64,75 %. The larval density in the eighth leaf has a medium average of 9,13, 15,83 medium and 1,90 pustules. The identified parasitoide was Meteorus sp, Elacherthus ceraminade, Cassinaria sp, Brachymeria sp and Hiperparasitoides of Cassinaria and non identified Brachymeria. The space distribution of Caterpillar the context of the Treasury Celia María with 320 has, you/he/she was of type agregativo with values from the superior variance to the half incidence expressed in larvas by leaf.